2017
DOI: 10.3390/ijms18040783
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Roles of IL-33/ST2 Axis in Renal Diseases

Abstract: Renal diseases, including acute kidney injury (AKI) and chronic kidney disease (CKD), have a great impact on health care systems worldwide. Similar to cardiovascular diseases, renal diseases are inflammatory diseases involving a variety of cytokines. Primary causes of renal injury include ischemia, uremic toxins, bacteremia, or nephrotoxicity. Inflammation represents an important component following kidney injury. Interleukin (IL)-33 is a member of the IL-1 cytokine family, which is widely expressed in epithel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 105 publications
(162 reference statements)
0
40
0
Order By: Relevance
“…IL-33 is mainly and constitutively expressed in the nuclei of epithelial barrier tissues and endothelial cells, and it can, therefore, be immediately released in response to cell injury. The few studies on the cellular localization of IL-33 in the kidney have documented a constitutive expression in endothelial nuclei of renal large and small vessels in humans 42 and also, peritubular vascular endothelial cells with a similar expression profile 21,23 in mice. In agreement with these data, we show here that, in healthy murine kidneys, IL-33 is mainly expressed by CD31(+) CD45(2) endothelial cells in peritubular capillaries and CD31(2) CD45(2) interstitial cells, which may be pericytes, endothelial progenitor cells, and/ or fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…IL-33 is mainly and constitutively expressed in the nuclei of epithelial barrier tissues and endothelial cells, and it can, therefore, be immediately released in response to cell injury. The few studies on the cellular localization of IL-33 in the kidney have documented a constitutive expression in endothelial nuclei of renal large and small vessels in humans 42 and also, peritubular vascular endothelial cells with a similar expression profile 21,23 in mice. In agreement with these data, we show here that, in healthy murine kidneys, IL-33 is mainly expressed by CD31(+) CD45(2) endothelial cells in peritubular capillaries and CD31(2) CD45(2) interstitial cells, which may be pericytes, endothelial progenitor cells, and/ or fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies have suggested that IL-33 is involved in the pathogenesis of kidney diseases and the associated tissue reparative responses [17,18]. For example, IL-33 level had increased in unilateral urinary obstruction (UUO) model in mice [19].…”
Section: Introductionmentioning
confidence: 99%
“…Unlike ST2L, sST2 lacks the transmembrane and cytoplasmic domains. sST2 has been associated with several diseases such as bronchial asthma, heart failure (HF), arthritis, sepsis in trauma patients, central nervous system (CNS) diseases, liver diseases and renal diseases . sST2 has been shown to be an efficient prognostic marker for patients with chronic HF .…”
Section: Introductionmentioning
confidence: 99%
“…sST2 has been associated with several diseases such as bronchial asthma, heart failure (HF), arthritis, sepsis in trauma patients, central nervous system (CNS) diseases, liver diseases and renal diseases. [6][7][8][9][10][11][12] sST2 has been shown to be an efficient prognostic marker for patients with chronic HF. 13 In spite of a large amount of data gathered in last decade for different biomarkers and their prognostic capacity, there are few studies that have assessed their effectiveness in ACS along with chronic noncardiovascular comorbidities.…”
Section: Introductionmentioning
confidence: 99%